Preparation method and application of gold nanoparticle loaded cerium monatomic material
By preparing gold nanoparticle-loaded cerium single-atom materials and combining them with microneedle delivery and photothermal therapy, the problems of poor stability of natural enzymes and limited delivery methods of anti-tumor drugs were solved, precise drug delivery to the tumor site and enhancement of multiple enzyme activities were achieved, with good biocompatibility and anti-tumor ability.
Patent Information
- Application Number
- CN202511042953.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-10-17
AI Technical Summary
Existing natural glucose oxidase has poor stability and is difficult to maintain activity in the tumor microenvironment. In addition, the existing anti-tumor drug delivery methods are not precise and continuous enough, resulting in limited therapeutic effects.
Cerium single-atom materials loaded with gold nanoparticles were prepared and delivered via microneedles, combined with photothermal therapy to achieve precise drug delivery to the tumor site and enhancement of multiple enzyme activities.
It achieves precise drug delivery and enhancement of multiple enzyme activities at the tumor site, has good biocompatibility and anti-tumor ability, can significantly reduce pH and produce harmful substances, promote tumor cell death, and photothermal therapy can achieve temperature control under 808nm near-infrared to avoid side effects on normal tissues.
Smart Images

Figure CN120788975A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of antitumor drug preparation, in particular to a preparation method and application of a cerium monatomic material loaded with gold nanoparticles. BACKGROUND
[0002] Glucose oxidase is a natural enzyme with good glucose oxidation ability and high catalytic specificity. However, the stability of the natural enzyme is poor, and it is easy to be inactivated in a complex tumor microenvironment. In addition, the preparation process of the natural enzyme is complex, and it is difficult to store, so the application range of the natural enzyme is narrow. The emergence of artificial enzymes just makes up for the shortcomings of natural enzymes, so artificial enzymes are often used to replace natural enzymes. Gold nanoparticles have good glucose oxidase (GOD) performance, and the GOD performance has size dependence. Gold nanoparticles (Au NPs) have good GOD and photothermal properties, and compared with glucose oxidase, they exhibit better stability at different temperatures and pH. The above excellent properties make gold nanoparticles widely used in the medical field.
[0003] Nowadays, the administration methods of tumor experiments are mainly tail vein injection and in situ injection. The drugs injected through the tail vein will circulate to the whole body, and a large dose of injection concentration will have toxic effects on the body and take a long time to act on the tumor site. Although intratumoral injection can act on the tumor site in time, the injected drugs cannot cover the entire tumor and the technology is difficult, which shows that the injection method is not the best administration method, and microneedle administration has certain advantages in this regard. Microneedle is a local administration method that can penetrate the stratum corneum, epidermis and dermis to play a role. Microneedles are mainly divided into solid microneedles, dissolvable microneedles and hollow microneedles. Among them, solid microneedles need additional wound dressing after transdermal, but the fine microneedle aperture wound and skin self-repairing lead to the inaccuracy of drug delivery. The additional physical operation required by hollow microneedles will cause inconvenience of self-administration, and needle waste will be generated. Dissolvable microneedles, i.e. the backing and needle can be quickly separated after transdermal, and the material can be dissolved by the organism to achieve the purpose of slow release, so as to realize accurate drug delivery. SUMMARY
[0004] In view of the above problems in the prior art, the present application provides a preparation method and application of a cerium monatomic material loaded with gold nanoparticles, which has good biocompatibility and antitumor ability, effectively solving the problems of poor stability of natural enzymes and limited administration method and insufficient treatment persistence of antitumor drugs.
[0005] To achieve the above object, the technical scheme adopted by the present application to solve its technical problems is: a preparation method of gold nanoparticle loaded cerium monatomic material is provided, comprising the following steps: S1, adding an aqueous solution of chloroauric acid, 3-mercaptopropionic acid and ammonia water into ultrapure water during stirring, then adding a sodium borohydride solution and stirring to obtain a mixed solution; S2, adding cerium monatomic atoms into the mixed solution obtained in step S1 and stirring, washing and drying the obtained precipitate to obtain the gold nanoparticle loaded cerium monatomic material.
[0006] Further, in step S1, the volume ratio of the aqueous solution of chloroauric acid, 3-mercaptopropionic acid, ammonia water, ultrapure water and sodium borohydride solution is 80-240 μL:10-30 μL:20-40 μL:20-40 μL:190-210 μL.
[0007] Further, in step S1, the volume ratio of the aqueous solution of chloroauric acid, 3-mercaptopropionic acid, ammonia water, ultrapure water and sodium borohydride solution is 160 μL:20 μL:30 μL:30 μL:200 μL.
[0008] Further, in step S1, the concentration of the aqueous solution of chloroauric acid is 0.04-0.06 g / mL -1 .
[0009] Further, in step S1, the concentration of the aqueous solution of chloroauric acid is 0.05 g / mL -1 .
[0010] Further, in step S1, the concentration of the sodium borohydride solution is 9-11 mg / mL -1 .
[0011] Further, in step S1, the concentration of the sodium borohydride solution is 10 mg / mL -1 .
[0012] Further, in step S1, the solution is stirred vigorously at room temperature for 1-1.5 h.
[0013] Further, in step S1, the solution is stirred vigorously at room temperature for 1 h.
[0014] The beneficial effects of adopting the above further scheme are: excessive sodium borohydride is decomposed.
[0015] Further, in step S2, the volume ratio of cerium monatomic atoms to the aqueous solution of chloroauric acid in step S1 is 0.9-1.1 mL:80-240 μL.
[0016] Further, in step S2, the volume ratio of cerium monatomic atoms to the aqueous solution of chloroauric acid in step S1 is 1 mL:160 μL.
[0017] Further, in step S2, the concentration of cerium monatomic atoms is 90-110 mg mL -1 .
[0018] Further, in step S2, the concentration of cerium monatomic atoms is 100 mg mL -1 .
[0019] Further, in step S2, the mass fraction of the loaded cerium monatomic atoms is 7.5 / 100.
[0020] Further, in step S2, the washing is performed 3-4 times with water and ethanol.
[0021] Further, in step S2, the washing is performed 3 times with water and ethanol.
[0022] Further, in step S2, the vacuum drying is performed at 55-65 ℃ for 11-13 h.
[0023] Further, in step S2, the vacuum drying is performed at 60 ℃ for 12 h.
[0024] The gold nanoparticle loaded cerium monatomic atom material is prepared by the method described above.
[0025] The gold nanoparticle loaded cerium monatomic atom material is used in the preparation of an antitumor drug.
[0026] A microneedle comprising the gold nanoparticle loaded cerium monatomic atom material described above.
[0027] The microneedle is prepared by the following method: dissolving the gold nanoparticle loaded cerium monatomic atom material in hyaluronic acid to obtain a needle body liquid, dropping the needle body liquid into a mold and flattening it, centrifuging, scraping off the needle body liquid on the surface of the mold, then spreading a substrate liquid, centrifuging and drying to obtain the microneedle.
[0028] Further, the mass to volume ratio of the gold nanoparticle loaded cerium monatomic atom material to hyaluronic acid is 35-45 mg:0.9-1.1 mL.
[0029] Further, the mass to volume ratio of the gold nanoparticle loaded cerium monatomic atom material to hyaluronic acid is 40 mg:1 mL.
[0030] Further, the concentration of hyaluronic acid is 14-16 wt%.
[0031] Further, the concentration of hyaluronic acid is 15 wt%.
[0032] Further, the mold is polydimethylsiloxane.
[0033] Further, the centrifugation is performed at 2900-3100 rpm min -1Centrifuged for 9-11 min.
[0034] Further, centrifuged at 3000 rpm min -1 Centrifuged for 10 min.
[0035] Further, the substrate solution is hyaluronic acid with a concentration of 19-21 wt%.
[0036] Further, the substrate solution is hyaluronic acid with a concentration of 20 wt%.
[0037] Further, dried in a blast oven at 35-45 ℃ for 4-6 h.
[0038] Further, dried in a blast oven at 40 ℃ for 5 h.
[0039] The present application has the following beneficial effects: 1. The gold nanoparticle loaded cerium monatomic material prepared by the method provided by the present application has good GOD-like performance and biocompatibility, wherein the synergistic gain effect of the gold nanoparticle and the cerium monatomic atom makes the gold nanoparticle loaded cerium monatomic material have significantly cascaded enzyme-like activity. Excellent GOD-like activity can consume glucose required for tumor cell metabolism, play a starvation treatment, reduce pH, and produce gluconic acid and hydrogen peroxide, which can promote the activity of 7.5 CeSAs / 1.0 Au NPs of the class POD, OD, CAT, and at the same time, the class GSH-Px performance adjusts the hypoxic environment to jointly cause cell death caused by lipid peroxidation of tumor cells.
[0040] 2. The gold nanoparticle loaded cerium monatomic material has photothermal performance, and good light-heat conversion efficiency makes 7.5 CeSAs / 1.0 Au NPs have the ability to synergistically treat tumors with light and heat, can realize accurate irradiation and temperature control of the tumor site under 808 nm near-infrared, and almost cause all tumor cells to die at 45 ℃, without side effects on normal tissues. In summary, 7.5 Ce SAs / 1.0 Au NPs have multiple cascade self-circulation enzyme activities and photothermal performance, have good biocompatibility and anti-tumor ability, and the anti-tumor performance is further improved by material delivery through microneedles, which has great potential in clinical applications. BRIEF DESCRIPTION OF DRAWINGS
[0041] Figure 1 is an HRTEM image of 7.5 Ce SAs / 1.0 Au NPs; Figure 2 is an HRTEM element distribution map of 7.5 Ce SAs / 1.0 Au NPs; Figure 3XRD patterns of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs; Figure 4 Graph of the results of the GOD-like enzyme activity of 7.5 Ce SAs / 1.0 Au NPs; Figure 5 Graph of the results of the POD-like enzyme activity of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs; Figure 6 Graph of the results of the POD-like enzyme activity of 7.5 Ce SAs / 1.0 Au NPs under different conditions; Figure 7 Graph of the results of the OD-like enzyme activity of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs; Figure 8 Graph of the results of the OD-like enzyme activity of 7.5 Ce SAs / 1.0 Au NPs under different conditions; Figure 9 Graph of the results of the GSH-Px-like enzyme activity of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs; Figure 10 Graph of the results of the GSH-Px-like enzyme activity of 7.5 Ce SAs / 1.0 Au NPs under different conditions; Figure 11 Graph of the results of the CAT-like enzyme activity of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs; Figure 12 Graph of the results of the CAT-like enzyme activity of 7.5 Ce SAs / 1.0 Au NPs under different temperatures and the oxygen production of hydrogen peroxide; Figure 13 Graph of the results of the photothermal performance of 7.5 Ce SAs / 1.0 Au NPs; Figure 14 Graph of a single photothermal heating and cooling curve when the power is 0.6 W cm -2 ; Figure 15 Graph of the biocompatibility of L929 cells co-incubated with different concentrations of 7.5 Ce SAs / Au NPs; Figure 16 Graph of the live / dead staining of 4T1 cells co-incubated with 7.5 Ce SAs / 1.0 Au NPs under different conditions; Figure 17 Graph of the results of the flow cytometry experiment of 4T1 cells co-incubated with 7.5 Ce SAs / 1.0 Au NPs under different conditions; Figure 18 Figures of tumor volume change of each group of mice under different conditions; Figure 19 Figures of H&E, Ki67, TUNEL staining of tumors after 14 days of treatment under different conditions; Figure 20 Figures of H&E staining of organs of 4T1 tumor-bearing mice after 14 days of treatment under different conditions. DETAILED DESCRIPTION
[0042] The principles and features of the present application are described below, and the examples are only used to explain the present application, and are not used to limit the scope of the present application. If the specific conditions are not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0043] Example 1 A preparation method of a gold nanoparticle-loaded cerium monatomic material, comprising the following steps: S1, 160 μL of an aqueous solution of chloroauric acid with a concentration of 0.05 g mL -1 , 20 μL of 3-mercaptopropionic acid and 30 μL of ammonia water are added to 30 μL of ultrapure water, then 200 μL of a sodium borohydride solution with a concentration of 10 mg mL -1 is added, and the mixture is stirred vigorously at room temperature for 1 h to obtain a mixed solution; S2, 1 mL of cerium monatomic material with a concentration of 100 mg mL -1 is added to the mixed solution obtained in step S1, and the mixture is stirred, and the obtained precipitate is washed with water and ethanol for 3 times and then vacuum dried at 60 ℃ for 12 h to obtain a gold nanoparticle-loaded cerium monatomic material (7.5 Ce SAs / 1.0 Au NPs).
[0044] Example 2 A preparation method of a gold nanoparticle-loaded cerium monatomic material, comprising the following steps: S1, 80 μL of an aqueous solution of chloroauric acid with a concentration of 0.04 g mL -1 , 10 μL of 3-mercaptopropionic acid and 20 μL of ammonia water are added to 20 μL of ultrapure water, then 190 μL of a sodium borohydride solution with a concentration of 9 mg mL -1 is added, and the mixture is stirred vigorously at room temperature for 1 h to obtain a mixed solution; S2, 0.9 mL of cerium monatomic material with a concentration of 90 mg mL -1Ce SAs to the mixed solution obtained in step S1, and stirred. The obtained precipitate was washed with water and ethanol for 3 times and vacuum dried at 55 ℃ for 11 h to obtain a gold nanoparticle loaded cerium monatomic material (7.5 Ce SAs / 0.5 Au NPs).
[0045] Example 3 A method for preparing a gold nanoparticle loaded cerium monatomic material, comprising the following steps: S1, 240 μL of an aqueous solution of chloroauric acid with a concentration of 0.06 g mL -1 , 30 μL of 3-mercaptopropionic acid and 40 μL of ammonia water were added to 40 μL of ultrapure water, and then 210 μL of a sodium borohydride solution with a concentration of 11 mg mL -1 was added, and stirred vigorously at room temperature for 1.5 h to obtain a mixed solution; S2, 1.1 mL of cerium monatomic atoms with a concentration of 110 mg mL -1 was added to the mixed solution obtained in step S1, and stirred. The obtained precipitate was washed with water and ethanol for 4 times and vacuum dried at 65 ℃ for 13 h to obtain a gold nanoparticle loaded cerium monatomic material (7.5 Ce SAs / 1.5 Au NPs).
[0046] Test Example 1 (1) The morphology of the gold nanoparticle loaded cerium monatomic material 7.5 Ce SAs / 1.0 Au NPs prepared in Example 1 was characterized by using a high-resolution transmission electron microscope (HRTEM), and the results are shown in Figure 1 , the energy dispersive spectroscopy (EDS) spectrum of the HRTEM of 7.5 Ce SAs / 1.0 Au NPs is shown in Figure 2 , and Figure 2 , wherein a is the HRTEM image of 7.5 Ce SAs / 1.0 Au NPs, and b is the EDS spectrum.
[0047] As can be seen from Figure 1 and Figure 2 , the cerium element is uniformly distributed in 7.5 Ce SAs / 1.0 Au NPs, there is no CeO2 lattice in 7.5 Ce SAs / 1.0 Au NPs and uniformly distributed Au NPs are observed, which proves the successful synthesis of 7.5 Ce SAs / 1.0 Au NPs.
[0048] Test Example 2 The XRD spectrum of 7.5 Ce SAs / 1.0 Au NPs prepared in Example 1 and 7.5 Ce SAs is shown in Figure 3 .
[0049] From Fig. 1, it can be seen that all materials have no characteristic peaks of CeO2, while 7.5 Ce SAs / 1.0 Au NPs shows the characteristic peaks of Au, which proves the successful loading of Au NPs on Ce SAs. Figure 3
[0050] Test Example 3 (1) The glucose oxidase (GOD) enzyme activity of 7.5 Ce SAs / 1.0 Au NPs was tested with TMB as a probe. The results are shown in Fig. 2, wherein the left graph is the pH change of the aqueous solution after 7.5 Ce SAs / 1.0 Au NPs catalyze glucose of different concentrations to produce gluconic acid, and the right graph is the GOD-like performance of 7.5 Ce SAs / 1.5 Au NPs at different temperatures. Figure 4 Figure 4
[0051] From Fig. 2, it can be seen that when the concentration of 7.5 Ce SAs / 1.0 Au NPs increases from 100 mM to 300 mM, the pH of the solution decreases from 5.75 to 5.52, which proves that the material can convert glucose to gluconic acid and further reduce the pH of the aqueous solution, and the reaction degree will increase with the increase of the concentration of glucose. With the temperature increasing from 37 ℃ to 42 ℃, the residual amount of glucose in the system decreases in turn. The above characterization proves that 7.5 Ce SAs / 1.0 Au NPs has good GOD-like performance, and the GOD-like performance will increase with the increase of temperature. Figure 4 (2) The peroxidase (POD) performance of 7.5 Ce SAs / 1.0 Au NPs was tested with TMB as a probe, and a control group was set. The comparison results of the POD-like performance of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs are shown in Fig. 3, wherein control is a blank control, CN is zeolitic imidazolate framework-8, 7.5 Ce SAs is cerium monatomic, and 7.5 Ce SAs / 1.0 Au NPs is 7.5 Ce SAs / 1.0 Au NPs prepared in Example 1. The POD-like performance of 7.5 Ce SAs / 1.0 Au NPs under different conditions is shown in Fig. 4, wherein the left graph is the influence of pH on the POD-like performance, and the right graph is the influence of temperature on the POD-like performance.
[0052] Figure 5 Figure 6 Figure 6
[0053] From Fig. 3 and Fig. 4, it can be seen that the POD-like performance of 7.5 Ce SAs / 1.0 Au NPs is better than that of 7.5 Ce SAs, and the POD-like performance of 7.5 Ce SAs / 1.0 Au NPs increases with the increase of pH and temperature. Figure 5 Figure 6 It can be seen that the introduction of Au NPs can enhance the POD-like performance of the material. At pH = 5.0, 7.5 CeSAs / 1.0Au NPs exhibits the best POD-like performance, and its performance gradually decreases with the increase of pH. The POD-like activity of 7.5 CeSAs / 1.0Au NPs increases with the increase of temperature until 42 ℃. Compared with 7.5 CeSAs, the introduction of Au NPs increases the optimum reaction temperature of the enzyme-like activity, so that 7.5 CeSAs / 1.0Au NPs exhibits better performance when combined with photothermal therapy.
[0054] (3) TMB was used as a probe to test the oxidase-like (OD) performance of 7.5 CeSAs / 1.0Au NPs. The comparison results of the OD-like performance of 7.5 CeSAs and 7.5 CeSAs / 1.0Au NPs are shown in Figure 7 , and the OD-like performance of 7.5 CeSAs / 1.0Au NPs under different conditions is shown in Figure 8 . Figure 8 Among them, the left figure is the influence of pH on the OD-like performance, and the right figure is the influence of temperature on the POD-like performance.
[0055] It can be seen from Figure 7 and Figure 8 that the additional introduction of Au NPs can enhance the OD-like performance of the material. At pH = 5.0, 7.5 CeSAs / 1.0Au NPs exhibits the best OD-like performance, and its performance gradually decreases with the increase of pH. The optimum reaction temperature increases with the increase of temperature until 42 ℃. In the treatment of tumors, combined with photothermal effect, it can promote the reaction to a greater extent.
[0056] (4) DTNB was used as an indicator to test the glutathione peroxidase-like (GSH-Px) performance of 7.5 CeSAs / 1.0Au NPs. The comparison results of the GSH-Px-like performance of 7.5 CeSAs and 7.5 CeSAs / 1.0Au NPs are shown in Figure 9 , and the GSH-Px-like performance of 7.5 CeSAs / 1.0Au NPs under different conditions is shown in Figure 10 . Figure 10 Among them, a is the influence of pH on the GSH-Px-like performance, and b is the influence of temperature on the GSH-Px-like performance.
[0057] It can be seen from Figure 9 and Figure 10It can be seen that due to the protective effect of Au NPs on GSH, the introduction of Au NPs slightly reduced the GSH-Px-like performance of the material. Despite the reduced enzyme-like activity, GSH was completely consumed in all three groups after 12 hours of reaction. At pH = 7.4, 7.5 Ce SAs / 1.0 Au NPs exhibited the best GSH-Px performance, which gradually decreased with decreasing pH. The optimal reaction temperature increased with increasing temperature between 37°C and 42°C. This indicates that combining Au NPs with photothermal therapy for tumor treatment can significantly promote the reaction and demonstrate stronger anti-tumor properties.
[0058] (5) The catalase (CAT) activity of 7.5 Ce SAs / 1.0 Au NPs was tested using a dissolved oxygen analyzer. The CAT performance comparison results of 7.5 Ce SAs and 7.5 Ce SAs / 1.0 Au NPs are shown in Figure 2. Figure 11 The CAT-like performance and hydrogen peroxide production of 7.5Ce SAs / 1.0 Au NPs at different temperatures are shown in Figure 2. Figure 12 As shown, Figure 12 In the middle, the left figure shows the CAT-like performance of 7.5 Ce SAs / 1.0 Au NPs at different temperatures, and the right figure shows the oxygen production of hydrogen peroxide at different temperatures.
[0059] Depend on Figure 11 and Figure 12 The introduction of Au NPs enhances the CAT-like properties of 7.5 Ce SAs / 1.0 Au NPs. This CAT-like property increases with increasing temperature. The degree of spontaneous decomposition of hydrogen peroxide is not significant at different temperatures, demonstrating that combining photothermal therapy with tumor treatment can significantly increase oxygen production and alleviate the tumor microenvironment.
[0060] Test Example 4 The photothermal performance of 7.5 Ce SAs / 1.0 Au NPs was tested at different power densities and concentrations. Figure 13 As shown, Figure 13 The left picture shows the concentration of 50 μg mL -1 Temperature changes of 7.5 Ce SAs / 1.0 Au NPs under different power illumination. The right figure shows the temperature change ... -2 Photothermal temperature changes of different concentrations of 7.5 Ce SAs / 1.0 Au NPs.
[0061] Depend on Figure 13 It can be seen that the photothermal performance of 7.5 Ce SAs / 1.0 Au NPs is related to the near-infrared light power density. -2Under 808 nm near-infrared irradiation, the concentration was 50 μg mL -1 The temperature of the 7.5 Ce SAs / 1.0 Au NPs solution reached about 40 °C within 5 min. -2 and 0.9 W cm -2 Under 808 nm near-infrared irradiation, the temperature reached about 50 °C and 65 °C within 5 min. As the concentration of 7.5 Ce SAs / 1.0 Au NPs increased from 50 μg mL -1 Gradually increase to 200 μg mL -1 , the final temperature of the solution gradually increased after 300 s of illumination.
[0062] The power is 0.6 W cm -2 When 7.5 Ce SAs / 1.0 Au NPs are irradiated with 808 nm near-infrared light, the temperature change of the single photothermal heating and cooling curves of different heating and cooling times are shown in Figure 2. Figure 14 shown.
[0063] Depend on Figure 14 It can be seen that the photothermal conversion efficiency of 7.5 Ce SAs / 1.0 Au NPs is 42.5% after calculation.
[0064] Test Example 5 The concentrations of 0, 12.5, 25, 50, 100 and 200 μg mL -1 L929 cells were co-incubated with 7.5 Ce SAs / Au NPs to test their biocompatibility. The results are as follows Figure 15 shown.
[0065] Depend on Figure 15 It can be seen that the concentration is 200 μg mL -1 The survival rate of L929 cells reached 80%. -1 It is the maximum concentration for biosafety.
[0066] Test Example 6 The anti-tumor activity of 7.5 Ce SAs / 1.0 Au NPs was detected by live / dead staining. 4T1 cells were cultured and then the medium was replaced with 7.5 Ce SAs / 1.0 AuNPs (200 μg mL -1) acidic RPMI 1640 (pH = 6.0) medium (7.5 Ce SAs / 1.0 Au NPs group, 7.5 Ce SAs / 1.0 Au NPs+H2O2 group). After incubation for 4 h, 7.5 Ce SAs / 1.0 Au NPs (200 μg mL -1 ) acidic RPMI 1640 (pH = 6.0) medium cells were incubated at 42 ℃, 45 ℃ for 10 min (7.5 Ce SAs / 1.0 Au NPs+H2O2 42 ℃ group, 7.5 Ce SAs / 1.0 Au NPs+H2O2 45 ℃ group). After removing the medium, the cells were washed twice with PBS and then stained with Calcein-AM / PI. The color development was observed by inverted fluorescence microscope, and the results are shown in Figure 16 Figure 16 , where A is the Control group, B is the H2O2 group, C is the 7.5 Ce SAs / 1.0 Au NPs group, D is the 7.5 Ce SAs / 1.0 Au NPs+H2O2, E is the 7.5 Ce SAs / 1.0 Au NPs+H2O2 42 ℃ group, F is the 7.5 Ce SAs / 1.0 Au NPs+H2O2 45 ℃ group. The temperature was kept at 10 min, and the concentration of 7.5 Ce SAs / 1.0 Au NPs was 200 μg mL -1 .
[0067] As can be seen from Figure 16 , 4T1 cells co-cultured with 7.5 Ce SAs / 1.0 Au NPs will undergo some cell death, and 4T1 cells co-cultured with 7.5 Ce SAs / 1.0 Au NPs in a simulated tumor microenvironment will be further killed by the enzyme-like reaction product, showing more red fluorescence than the 7.5 Ce SAs / 1.0 Au NPs group. In 4T1 cells co-cultured with 7.5 Ce SAs / 1.0 Au NPs, photothermal therapy was performed at different temperatures. At 42 ℃, a large amount of red fluorescence was shown. At 45 ℃, there was almost no green fluorescence, and the most red fluorescence was shown in all components, proving the massive death of cells.
[0068] The 4T1 cells of the above different components were detected for apoptosis using Annexin V-FITC / PI cell apoptosis detection kit. After staining, flow cytometry was performed for detection, and Flowjo software was used for data processing. The results of 4T1 flow cytometry experiment co-incubated with 7.5 Ce SAs / 1.0 Au NPs under different conditions are shown in Figure 17 Figure 17 In the figure, A is the control group, B is the H2O2 group, C is the 7.5 Ce SAs / 1.0 Au NPs group, D is the 7.5 Ce SAs / 1.0 Au NPs+H2O2, E is the 7.5 Ce SAs / 1.0 Au NPs+H2O242℃ group, and F is the 7.5 Ce SAs / 1.0 Au NPs+H2O245℃ group. The temperature was maintained for 10 min, and the concentration of 7.5 Ce SAs / 1.0 Au NPs was 200 μg mL -1 Group.
[0069] Depend on Figure 17 It can be seen that the viability of 4T1 cells was not affected in the simulated tumor microenvironment. The apoptosis rate of cells co-cultured with 7.5 Ce SAs / 1.0 Au NPs in the simulated tumor microenvironment increased by approximately 10%. Based on this, photothermal therapy was performed at different temperatures. The 4T1 cell survival rates in the 7.5 Ce SAs / 1.0 Au NPs+H2O242°C group and the 7.5 Ce SAs / 1.0 Au NPs+H2O245°C group were 32.6% and 23.4%, respectively. Among them, the 7.5 Ce SAs / 1.0 Au NPs+H2O245°C group showed the lowest cell survival rate among all components, demonstrating the joint anti-tumor effect of temperature and heat-promoting enzyme performance expression.
[0070] Test Example 7 PBS containing 4T1 cells was injected into the hind legs of mice (about 1 × 10 cells per mouse). 6 cells), and the tumor volume reached 80 mm 3 The mice were randomly divided into four groups to establish a tumor-bearing mouse model. After successful modeling, 20 4T1 tumor-bearing mice were randomly divided into five groups: (1) control group, (2) 7.5 Ce SAs / 1.0 Au NPs injection group (7.5 Ce SAs / 1.0 Au NPs), (3) 7.5 Ce SAs / 1.0 Au NPs microneedle treatment group (7.5 Ce SAs / 1.0 Au NPs MNs), (4) 7.5 Ce SAs / 1.0 AuNPs 42 ℃ microneedle treatment group (7.5 Ce SAs / 1.0 Au NPs MNs 42℃), (5) 7.5 Ce SAs / 1.0 Au NPs 45 ℃ microneedle treatment group (7.5 Ce SAs / 1.0 Au NPs MNs 45℃), with 5 mice in each group. When the tumor volume reached 50 mm 3 When the second group was injected with 7.5 Ce SAs / 1.0 Au NPs (5 mg kg -1Meanwhile, the 3rd group, the 4th group and the 5th group were treated with microneedles, and the 4th group and the 5th group were irradiated with 808 nm near-infrared light for 10 min, and the temperature was controlled at 42 ℃ and 45 ℃ respectively, and an infrared thermometer was used to take infrared images every 2 min.
[0071] The BALB / C strain mice (female, 8 weeks, 20) used were from Beijing Charles River Experimental Animal Technology Co., Ltd.
[0072] The preparation method of the microneedle includes the following steps: dissolving the cerium monatomic material loaded with gold nanoparticles (7.5 Ce SAs / 1.0 Au NPs) in 15wt% hyaluronic acid to obtain a needle body liquid, using polydimethylsiloxane as a mold, dropping the needle body liquid into the mold and flattening, centrifuging at 3000 rpm min -1 After centrifugation for 10 min, the needle body liquid on the surface of the mold was scraped off, and then 20wt% hyaluronic acid was evenly spread, and centrifuged at 3000 rpm min -1 After centrifugation for 10 min, dry in a 40 ℃ air oven for 5 h to obtain microneedles (7.5 Ce SAs / 1.0 Au NPs MNs).
[0073] The above experiment was carried out on the 1st, 3rd, 5th and 7th days, and the tumor volume and body weight were measured every 2 days, for a total of 14 days. The tumor volume calculation formula is: V = 0.52 × a × b 2 In the above formula, a is the long diameter of the tumor (the longest diameter), and b is the short diameter of the tumor (the shortest diameter perpendicular to the long diameter).
[0074] The tumor volume changes of the mice in each group are shown in Figure 18 Figure 18 Among them, Control is the control group, 7.5 Ce SAs / 1.0 Au NPs is the 7.5 Ce SAs / 1.0 Au NPs injection group, 7.5 Ce SAs / 1.0 Au NPs MNs is the 7.5 Ce SAs / 1.0 Au NPs microneedle treatment group, 7.5 Ce SAs / 1.0 Au NPs MNs 42 ℃ is the 7.5 Ce SAs / 1.0 Au NPs 42 ℃ microneedle treatment group, and 7.5 Ce SAs / 1.0 Au NPs MNs 45 ℃ is the 7.5 Ce SAs / 1.0 Au NPs 45 ℃ microneedle treatment group.
[0075] From Figure 18 It can be seen that the anti-tumor ability of the 7.5 Ce SAs / 1.0 Au NPs MNs group is more significant than that of the 7.5 Ce SAs / 1.0 Au NPs in situ injection, and the combination of 7.5 Ce SAs / 1.0 Au NPs MNs and photothermal therapy can significantly inhibit the growth of tumors, and the tumor volume is obviously inhibited, and there is almost no obvious tumor after the treatment cycle.
[0076] After 14 days, the mice were sacrificed, and the tumors and organs (heart, lung, liver, spleen, kidney) were taken. All tissues were soaked in 4% paraformaldehyde solution for preservation. Hematoxylin and eosin (H&E) staining was used to stain the tumors and main organs. In addition, the tumors were evaluated by immunohistochemical (TUNEL) staining and immunofluorescence (Ki67) analysis. H&E staining of tumor tissue reflects the degree of tumor cell necrosis. Ki67 indicates the degree of tumor cell proliferation. TUNEL staining shows the degree of apoptosis. The results of H&E, Ki67, and TUNEL staining of tumors after different conditions for 14 days are shown in FIGS. 8A-8C, respectively. Figure 19 The results of H&E staining of organs of 4T1 tumor-bearing mice after different conditions for 14 days are shown in FIG. 9. Figure 20 Figure 20 In FIG. 8A, A is Control, B is 7.5 Ce SAs / 1.0 Au NPs, C is 7.5 Ce SAs / 1.0 Au NPs MNs, D is 7.5 Ce SAs / 1.0 Au NPs MNs 42 °C, and E is 7.5 Ce SAs / 1.0 Au NPs MNs 45 °C.
[0077] As can be seen from FIG. 8A, the degree of tumor cell necrosis in the 7.5 Ce SAs / 1.0 Au NPs MNs group is more obvious than that in the 7.5 Ce SAs / 1.0 Au NPs injection group, the 7.5 Ce SAs / 1.0 Au NPs MNs 42 °C group has a stronger destructive effect on tumor cells, and the 7.5 Ce SAs / 1.0 Au NPs MNs 45 °C group has the strongest anti-tumor ability. Figure 19 As can be seen from FIG. 8B, the 7.5 Ce SAs / 1.0 Au NPs MNs group has more brown spots in the Ki67 staining, and the 7.5 Ce SAs / 1.0 Au NPs MNs 45 °C group has the most brown spots, further confirming the synergistic anti-tumor effect of 7.5 Ce SAs / 1.0 Au NPs in vivo, which can not only destroy tumor cells but also prevent tumor cell proliferation.
[0078] As can be seen from FIG. 8C, the 7.5 Ce SAs / 1.0 Au NPs MNs group has more green fluorescence in the TUNE staining, and the 7.5 Ce SAs / 1.0 Au NPs MNs 45 °C group has the most green fluorescence, further confirming the synergistic anti-tumor effect of 7.5 Ce SAs / 1.0 Au NPs in vivo, which can not only destroy tumor cells but also prevent tumor cell proliferation. Figure 20 It can be seen that by observing the H&E staining sections of the heart, liver, spleen, lung and kidney of each group, it can be seen that 7.5 CeSAs / 1.0 Au NPs injection and 7.5 CeSAs / 1.0 Au NPs MNs combined with 808 nm near-infrared laser irradiation have no obvious side effects on organs, which not only proves the good biocompatibility and excellent anti-tumor performance of 7.5 CeSAs / 1.0 Au NPs, but also shows that 7.5 CeSAs / 1.0 Au NPs has good clinical application potential.
[0079] The above description is only the preferred embodiment of the present application, and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a cerium single-atom material supported by gold nanoparticles, characterized in that: The following steps are involved: S1. Adding chloroauric acid aqueous solution, 3-mercaptopropionic acid and ammonia water to ultrapure water while stirring, and then adding sodium borohydride solution and stirring to obtain a mixed solution; S2. Adding cerium single atoms to the mixed solution obtained in step S1, stirring, washing the obtained precipitate and drying it to obtain a cerium single atom material loaded with gold nanoparticles.
2. The method for preparing the gold nanoparticle-loaded cerium single-atom material according to claim 1, wherein: In step S1, the volume ratio of the chloroauric acid aqueous solution, 3-mercaptopropionic acid, ammonia water, ultrapure water, and sodium borohydride solution is 80-240 μL:10-30 μL:20-40 μL:20-40 μL:190-210 μL.
3. The method for preparing the gold nanoparticle-loaded cerium single-atom material according to claim 1, wherein: In step S1, the concentration of the chloroauric acid aqueous solution is 0.04-0.06 g mL -1 .
4. The method for preparing the gold nanoparticle-loaded cerium single-atom material according to claim 1, wherein: In step S1, the concentration of sodium borohydride solution is 9-11 mg mL -1 .
5. The method for preparing the gold nanoparticle-loaded cerium single-atom material according to claim 1, wherein: In step S2, the volume ratio of the cerium single atom to the aqueous chloroauric acid solution in step S1 is 0.9-1.1 mL:80-240 μL.
6. The method for preparing the gold nanoparticle-loaded cerium single-atom material according to claim 1, wherein: In step S2, the concentration of cerium atoms is 90-110 mg mL -1 .
7. A gold nanoparticle-loaded cerium single-atom material prepared by the method for preparing a gold nanoparticle-loaded cerium single-atom material according to any one of claims 1 to 6.
8. Use of the gold nanoparticle-loaded cerium single atom material according to claim 7 in the preparation of anti-tumor drugs.
9. A microneedle, characterized in that: The cerium single atom material comprising the gold nanoparticles as claimed in claim 7.
10. The method for preparing the microneedle according to claim 9, characterized in that: The method comprises the following steps: dissolving cerium single atom material loaded with gold nanoparticles in hyaluronic acid to obtain needle body fluid, dropping the needle body fluid into a mold and spreading it flat, after centrifugation, scraping off the needle body fluid on the surface of the mold, then spreading the mold with substrate fluid, centrifuging and drying to obtain microneedles.